(untitled) (International Current Pharmaceutical Journal, 2014)
The aim of this study was to evaluate the suspending properties of Brachystegia eurycoma gum on metronidazole suspension. The suspending properties of Brachystegia eurycoma gum (family leguminosae) were evaluated comparatively with that of compound tragacanth powder at concentration range of 2.5 10.0%w/v in metronidazole suspension. The following parameters were determined; sedimentation volume (%), viscosity, pH and re-dispersion number. The values obtained were used as basis for comparison of the suspending agents studied. Brachystegia eurycoma and compound tragacanth gums had a pH range between 4.7 to 4.9 and between 3.9 to 4.1 respectively which indicates that they are slightly acidic. Particles suspended with tragacanth gum at concentration ? 7.5%w/w redispersed easily than those formulated with the Brachystegia eurycoma gum at ? 10% w/w. It was observed that with increase in concentration of the gum the viscosity of the suspension increased correspondingly. For instance, at concentration of 2.5%w/w viscosities of the suspensions are 490 poise (Brachystegia eurycoma gum) and 603 poise (compound tragacanth gum) while at concentrations of 7.5%w/w their viscosities were 914 poise (Brachystegia eurycoma gum) and 1709 poise (compound tragacanth gum). There was a direct proportionality between viscosity of the gums at different concentrations and the sedimentation rate of the suspensions, as the viscosity of the gum increases, the rate of sedimentation of the suspension decreases. Brachystegia eurycoma gum at predetermined concentration can be exploited as an alternative excipient in the formulation of pharmaceutical suspensions of insoluble substances. DOI: http://dx.doi.org/10.3329/icpj.v3i11.20727 International Current Pharmaceutical Journal, October 2014, 3(11): 328-330